The role of family and school in the formation of the culture of thought, cultural identity and tolerance of personality in young people - Kovalchuk, Larysa (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
Under the conditions of the intensive processes of globalization and integration in the modern world the problem of forming of culture of thought of the young person, his/her cultural identity and tolerance acquires special actuality. The essence of culture which is one of the fundamental categories of the modern humanitarian discourse is presented in the article. The approaches of researchers to the interpretation of the concepts “the culture of thought”, “the cultural identity of personality” and “tolerance” in pedagogy, psychology and sociology are analysed.
Keywords: culture; culture of thought; cultural identity; tolerance; family; school